The Influence of Self-Efficacy and Achievement Motivation on Physics Learning Outcomes of Class X Students at SMA Negeri in Bulukumba - Nur Ika Akbar; Khaeruddin; Pariabti Palloan (Postgraduate, University of Mataram, 2025)
This research is a survey study that aims to analyze the direct and indirect effects of several variables. Sampling is done using a cluster sampling technique, assuming that all schools are relatively homogeneous, resulting in a sample size of 320 students from SMA Negeri in Bulukumba. The data is obtained through self-efficacy questionnaires instruments, achievement motivation questionnaires, and physics learning outcome tests. The collected data will be processed using two types of analysis techniques, namely descriptive analysis and inferential analysis, using path analysis. The descriptive analysis concludes that students self-efficacy, achievement motivation, and physics learning outcomes are all in the high category. Additionally, the inferential analysis concludes that: self-efficacy have a direct and significant positive effect on physics learning outcomes of students, self-efficacy have a direct and significant positive effect on achievement motivation of students, achievement motivation has a direct and significant positive effect on physics learning outcomes of students, and self-efficacy have an indirect and significant positive effect on physics learning outcomes through achievement motivation of students.